1996
DOI: 10.1002/(sici)1097-0045(199603)28:3<172::aid-pros4>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of the nucleoside analogue gemcitabine on prostatic carcinoma cells

Abstract: Gemcitabine (2≺,2≺difluoro‐2≺deoxycytidine, dFdC) is a synthetic antimetabolite of the cellular pyrimidine nucleotide metabolism. In a first series of in vitro experiments, the drug showed a strong effect on the proliferation and colony formation of the human androgen‐sensitive tumor cell line LNCaP and the androgen‐insensitive cell lines PC‐3 and DU‐145. Maximal inhibition occurred at a dFdC concentration as low as 30 nM. In contrast to the cell lines which were derived from metastatic lesions of prostate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 8 publications
2
12
0
2
Order By: Relevance
“…They were grown in medium containing 10% CS FCS for 24 h. After this period, the concentration of CS FCS was reduced to 5% and either androgen or one of the non-steroidal anti-androgens (hydroxyflutamide, bicalutamide) was added. Proliferative response was assessed after 72 h. The MTT assay was performed as recently described by Cronauer et al (1996).…”
Section: Assessment Of In Vitro Proliferation Of Lncap Cellsmentioning
confidence: 99%
“…They were grown in medium containing 10% CS FCS for 24 h. After this period, the concentration of CS FCS was reduced to 5% and either androgen or one of the non-steroidal anti-androgens (hydroxyflutamide, bicalutamide) was added. Proliferative response was assessed after 72 h. The MTT assay was performed as recently described by Cronauer et al (1996).…”
Section: Assessment Of In Vitro Proliferation Of Lncap Cellsmentioning
confidence: 99%
“…It has been reported, indeed, that in some human solid tumors, cells were blocked in the S phase depending on the exposure time and chemotherapeutic concentration (Cronauer et al 1996, Ng et al 2000. In contrast, other authors reported an arrest in G 1 phase only depending on the dFdCyd concentration.…”
Section: Tablementioning
confidence: 99%
“…This study provides important new insights into the effects of inhibiting NF-KB in TNF-a-insensitive prostate cancer cells. A wide range of intracellular components are implicated in TNF-a-induced cell killing, including pertussis toxin-sensitive guanine nucleotide binding protein (34), phospholipase A2 (35), phospholipase D activation (36), and DNA damage (37). Despite which receptor sets off the cytotoxic effect, the various intracellular signals activated by TNF-a lead to activation of NF-KB (4).…”
Section: + +mentioning
confidence: 99%
“…A study by Cronauer et al examine gemcitabine as a single agent in the in vitro treatment of the PC-3, DU-145 and LNCaP human prostate cancer cell Ones (34). Their results demonstrated gemcitabine had a strong effect on the prostate cancer cell lines, but did not effect normal epithelial cell growth (34).…”
Section: + +mentioning
confidence: 99%
See 1 more Smart Citation